God created the integers : the mathematical breakthroughs that changed history - Hawking, S. W. (Stephen W.) (Running Press, 2007)
Bestselling author and physicist Hawking explores the "masterpieces" of mathematics, 25 landmarks spanning 2,500 years and representing the work of 15 mathematicians, including Augustin Cauchy, Bernard Riemann, and Alan Turing.